Analysis of quality dynamics in the fermentation of metata ayib: a traditional Ethiopian spiced hard cheese - Aleme Asresie; Dawudie Gobezie; Ulfina Gelmessa (Applied Food Research)
This study examined the changes in physicochemical, microbial quality and safety, mineral and organoleptic quality dynamics of metata ayib during the fermentation process. Conducted using a completely randomized design, the experiment comprised six distinct treatments. The metata ayib samples under took analysis for various attributes, including physicochemical properties (pH, fat, protein, ash, titratable acidity, carbohydrates, and moisture), microbial quality (total counts, yeast and mold, lipolytic, lactic acid, and proteolytic bacteria), microbial safety testing for (Enterobacteriaceae, Salmonella, Staphylococcus aureus, and Escherichia coli O157:H7), and mineral content (calcium, magnesium, sodium, potassium, and phosphorus). Standard laboratory techniques were employed for these evaluations. Additionally, sensory analysis was performed by consumer panelists to gauge taste, aroma, color, texture, and overall acceptability. All data were analyzed using SAS software. The results showed that with an increase in fermentation time, there were significant increases (p < 0.05) in fat, protein, ash, and titratable acidity. In contrast, carbohydrate, moisture, and pH levels significantly decreased (p < 0.05). Additionally, the total counts of bacteria, yeast and mold, lipolytic bacteria, and proteolytic bacteria significantly declined (p < 0.05) during fermentation, while the number of lactic acid bacteria increased significantly (p < 0.05). Notably, coliforms, Enterobacteriaceae, Salmonella, Staphylococcus aureus, and E. coli O157:H7 were not detected at any stage of the fermentation process. The mineral content, including calcium, magnesium, sodium, potassium, and phosphorus, also showed significant increases (p < 0.05). Sensory evaluations demonstrated significant enhancements in taste, color, texture, aroma, appearance, and overall acceptability (p < 0.05) throughout fermentation. Overall, the findings indicate that metata ayib fermented for 25 days exhibited improved physicochemical properties, mineral content, microbiological quality, safety, and sensory characteristics compared to shorter fermentation periods. The duration of fermentation is vital for enhancing the nutritional value and microbial quality of metata ayib, ultimately leading to greater consumer acceptance. Further research is necessary to explore the impacts of spice ratios, fermentation duration, fatty acid and amino acid profiles, and the selection of predominant lactic acid bacteria as starter cultures to support the commercialization of metata ayib production.